REPRESENTATION OF SM OPERATORS ON SEQUENCE SPACES WITH A NEW NORM - Ansori, Muslim (MATEMATIKA, 2011)
We give some representations of SM-operator on sequence spaces , using a new norm different from that of ones in the beginning and some examples are given